The Effect of The Use of E-Learning Technology (Media LCD Projector) on The Achievement of Class IX SKI Lessons at Islamic Junior High School 2 Ponorogo - Miftahul Ulum; Abid Hifni Muhammad (Educan : Jurnal Pendidikan Islam, 2020)
The rapid development of technology in various fields has also been felt in the world of education. This development can be seen from the rise of the use of computers as teaching aids as well as learning media. What is mean by teaching aids here are tools or objects used by teachers to facilitate teaching tasks such as helping in calculating or analyzing data. While the learning media in question is the use of a computer connected to the LCD projector media to facilitate students in understanding the material. This study aims to find out 1) How to use e-learning technology LCD projector media on the subjects of SKI in MTsN 2 Ponorogo. 2) Is there any influence between e-learning media projector LCD technology on SKI learning achievement in MTsN 2 Ponorogo. This research is an experimental quantitative research. Data collection is done by documenting grades in school. Data collection is done by looking at the results of the midterm exam between two classes namely the experimental class and the control class, then analyzing the results of all student grades and then finally given a conclusion. The results of this study indicate that the application of projector LCD media in SKI learning is declared effective again student learning achievement as evidenced by the results of the student’s midterm examination which shows that the projector LCD media is very useful as a supporting medium in learning the history of Islamic culture.